Feedback stabilization of continuous systems by adding an integrator - Outbib, Rachid; Aggoune, Woihida (Zielona Góra: Uniwersytet Zielonogórski)
This note is devoted to the problem of global stabilization of continuous systems by adding an integrator. The goal is to prove that if a continuous non-linear system ?x = f(x, u)? is globally asymptotically stable at the origin for ?u ? 0?, then the augmented system obtained by adding an integrator is stabilizable by means of a continuous feedback.
Keywords: feedback stabilization; nonlinear systems; continuous systems; Lyapunov function